Exploring travel for work-life balance: a study on solo woman travellers in bali - Wiwiek Agustina, Ni Ketut; Julio, I Kadek Nora; Argapura, Kadek Kresna (Journal of Business on Hospitality and Tourism, 2022)
With the importance of balance in life, the phenomenon of work-life balance is very engaging to be associated with travelling activities, especially solo travel, which became popular during the COVID-19 pandemic as a new trend that emerged. This research aims to analyse the phenomenon of travelling for work-life balance, whether it can be a trend or lifestyle, using an exploratory study approach that focuses on solo women travellers in Bali, especially those from Denpasar City and Badung Regency. Qualitative descriptive methods were used in this study, with data collection techniques through literature studies, observations, and comprehensive interviews of 13 informants consisting of 10 primary informants, 2 key informants, and 1 supporting informant. The selection of informants is carried out using purposive sampling techniques with the Pentahelix approach. With the selection of the primary informant criteria, namely, solo woman travellers in Bali aged 18-26 years, and the criteria of key informants and supporters are academics that have insights into the field of travel, especially in women travellers. The results showed that travelling activities have a strong and significant influence in building new behaviour patterns towards women travellers in Bali in doing solo travelling activities to achieve work-life balance.  The need for healing activities for their lives and performance become a motivation and desire that every solo woman traveller in Bali wants to realise. Travelling for work-life balance plays a vital role in achieving productivity and can be a workable lifestyle.